Malawian gets food security award - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
For her work on breeding Open Pollinated Varieties (OPVs) of maize, Malawian scientist Elizabeth Minofu Sibale has won the 2000 award from the World Bank Group and IMF Africa Club. Sibale, who received the award in January 2001, is renowned for her...